Veratrilla baillonii Franch Ameliorates Diabetic Liver Injury by Alleviating Insulin Resistance in Rats - Zhang, Zhi-Hao; Li, Juan; Li, Jun; Ma, Zhaowu; Huang, Xian-Ju (Frontiers in Pharmacology, 2021)
Type 2 diabetes mellitus (T2DM) is a complex and polygenic disorder with diverse complications. Veratrilla baillonii Franch (V. baillonii,) has been applied in the intervention and treatment a diverse range of diseases, including diabetes. In this study, we revealed that water extracts of V. baillonii (WVBF) can ameliorate liver injury and insulin resistance in T2DM rat model. To elucidate the anti-diabetic mechanisms of WVBF, we performed liver transcriptome analysis that displayed WVBF treatment significantly suppressed many gene expressions involved in insulin resistance. Furthermore, functional experiments showed that WVBF treatment reduced the pathological damages of liver and pancreas, which may be regulated by Foxo1, Sirt1, G6pc, c-Met, Irs1, Akt1, Pik3r1. These results indicated that WVBF improves diabetic liver injury and insulin resistance in diabetic rats. Therefore, this study demonstrated WVBF could be used as a promising therapeutic agent for intervention and treatment of diabetes.